2018
DOI: 10.1186/s13071-018-2808-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of desiccation stress on adult female longevity in Aedes aegypti and Ae. albopictus (Diptera: Culicidae): results of a systematic review and pooled survival analysis

Abstract: BackgroundTransmission dynamics of mosquito-borne viruses such as dengue, Zika and chikungunya are affected by the longevity of the adult female mosquito. Environmental conditions influence the survival of adult female Aedes mosquitoes, the primary vectors of these viruses. While the association of temperature with Aedes mortality has been relatively well-explored, the role of humidity is less established. The current study’s goals were to compile knowledge of the influence of humidity on adult survival in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(59 citation statements)
references
References 139 publications
0
57
0
2
Order By: Relevance
“…Saturation deficit, derived from temperature and humidity measurements was used. It is the deficit between the amount of moisture in the air and the amount of moisture the air can hold when it is saturated, making it a more meaningful measure for micro-climatic effects on insects which try to avoid desiccation 42,43 . Host-choice of An.…”
Section: Resultsmentioning
confidence: 99%
“…Saturation deficit, derived from temperature and humidity measurements was used. It is the deficit between the amount of moisture in the air and the amount of moisture the air can hold when it is saturated, making it a more meaningful measure for micro-climatic effects on insects which try to avoid desiccation 42,43 . Host-choice of An.…”
Section: Resultsmentioning
confidence: 99%
“…albopictus spread first to the islands in the Indian and Pacific Oceans 3 and, during the 1980s, rapidly extended its range across temperate regions in Europe, the Americas and Africa 1,4 . This mosquito is able to tolerate climate/environment interactions that differ from its home range [5][6][7] . Its ability to diapause during unfavourable seasons and to lay desiccation-resistant eggs has facilitated its expansion in temperate regions [8][9][10][11] .…”
mentioning
confidence: 99%
“…Our findings show a positive association between temperature and the number of Aedes sp based on Pearson’s correlations analysis. Tsai et al [37] found that critically low (as low as 13.8°C) and higher temperatures may decrease the mosquito populations, with regards to the mosquito’s fertility and longevity [38]. Other studies on diurnal temperature found a significant interaction between larval density and temperature settings.…”
Section: Discussionmentioning
confidence: 99%